Pengaruh Digital Marketing Pada Instagram Dalam Membangun Brand Image Janjian Coffee Roasters - Zakaria, Fachri Syam; Anindita Lintangdesi A (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This study aims to analyze the effect of digital marketing on brand image at Janjian Coffee Roasters Coffee Shop in West Java. Coffee shop business actors use the benefits of advances in existing information and communication technology, including social media, to market their business. Social media can influence economic development because it enables marketing communications and buying and selling transactions between producers and consumers. The digital marketing phenomenon uses social media to promote products globally and can improve brand image. This research is quantitative and descriptive. In this study, a questionnaire was distributed to one hundred consumers of Janjian Coffee Roasters Coffee Shop. This study uses simple random sampling data collection techniques. Simple Random Sampling is the taking of sample members from a population that is carried out randomly without regard to the strata in that population. The results of this study indicate that there is a positive influence of digital marketing on brand image. The better digital marketing can improve brand image. This is shown that Janjian Coffee Roasters' social media is interesting to follow, which can create a well-recognized Janjian Coffee Image.